A green route to methyl acrylate and acrylic acid by an aldol condensation reaction over H-ZSM-35 zeolite catalysts. Issue 65 (28th July 2017) - Ma, Zhanling; Ma, Xiangang; Liu, Hongchao; He, Yanli; Zhu, Wenliang; Guo, Xinwen; Liu, Zhongmin
Abstract : An aldol condensation reaction was first conducted with DMM and MAc over zeolite catalysts to produce MA and AA. Abstract : A one-step aldol condensation reaction to produce MA and AA is a green and promising strategy. Here, the aldol condensation reaction was first conducted with DMM and MAc over different types of zeolite catalysts. The H-ZSM-35 zeolite demonstrates excellent catalytic performance with a DMM conversion of 100% and a MA + AA selectivity of up to 86.2% and superior regeneration ability, with great potential for industrial operation.